Diagnosis of the 2002 study plan of the bachelor in modern Languages with Specialization in French and English of the University of El Salvador - Pérez Orellana, Claudia Lisseth; Peralta Rivas, Gabriela; Salamanca Corvera, Josseline Beatriz (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2024)
Disponible en formato impreso